Composite metamorphic history recorded in garnet porphyroblasts of Sambagawa metasediments in the Besshi region, central Shikoku, Southwest Japan. (5th November 2014) - Kouketsu, Yui; Enami, Masaki; Mouri, Takashi; Okamura, Mitsuya; Sakurai, Tsuyoshi
Abstract This report describes an investigation of the composite metamorphic history recorded in garnet porphyroblasts of Sambagawa metasediments, and presents discussions of the possible distribution of eclogite facies lithologies in the Besshi region, central Shikoku, southwest Japan. Garnet grains usually show chemically composite zoning with resolved inner and overgrown outer segments, respectively. The inner segment usually contains paragonite as a sodic phase inclusion and rarely contains omphacite or glaucophane, whereas the outer segment rarely includes albite but no paragonite. The inner segment often includes quartz grains that preserve high residual pressures corresponding to the eclogite facies conditions, whereas the outer segment includes quartz grains that preserve lower residual pressures corresponding to the epidote–amphibolite facies conditions. For this composite‐zoned garnet, the assemblage of sodic phase inclusions and the values of the residual pressure of quartz inclusions imply the following successive metamorphic path: prograde eclogite facies stage → decompression and hydration reaction stage → prograde epidote–amphibolite facies stage. Metasediments containing this composite‐zoned garnet with such evidence for eclogite facies conditions are more widely distributed than the eclogitic lithologies that contain the assemblage of omphacite + garnet. These results imply that the combination of (i) the chemical composite zoning of garnet, (ii) the nature of sodic phase inclusions, and (iii) the residual pressure of quartz inclusions is useful as criteria to ascertain the true distribution of the lithologies that have experienced eclogite facies metamorphism for the Sambagawa metasediments, which was difficult to recognize in earlier studies.